2004
DOI: 10.1590/s0102-33062004000200004
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de plantas jovens de Tabebuia aurea (Manso) Benth. & Hook. f. ex S. Moore submetidas a estresse hídrico

Abstract: Tabebuia aurea (Manso) Benth. & Hook. f. ex S. Moore pertence à família Bignoniaceae e ocorre nas margens dos rios temporários do Nordeste semi-árido. O crescimento das plantas jovens foi acompanhado em casa de vegetação por quatro meses e foi analisado em função do alongamento (cm), massa da matéria seca (g) e densidade estomática (mm²). Trinta dias após a semeadura, as plantas foram submetidas a três tratamentos hídricos: 100, 50 e 25% da capacidade de campo (cc). A densidade estomática foi verificada me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
25

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 9 publications
2
15
0
25
Order By: Relevance
“…Depending on the species, cotyledons can contain large amount of reserve compounds that are consumed during germination and early growth of the plant (Santos & Buckeridge 2004;Corte et al 2006). The long-term persistence of cotyledons in tropical woody species has been reported in several studies, as in Cabral et al (2004), who verified that cotyledons remained for 120 days attached to plants of Tabebuia aurea. Similarly, studies have shown that seedlings of M. urundeuva are able to maintain the cotyledons for a period of 90 days (Figueirôa et al 2004), while K. coriacea cotyledons may remain attached to the plant for up to six months (Nardoto et al 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Depending on the species, cotyledons can contain large amount of reserve compounds that are consumed during germination and early growth of the plant (Santos & Buckeridge 2004;Corte et al 2006). The long-term persistence of cotyledons in tropical woody species has been reported in several studies, as in Cabral et al (2004), who verified that cotyledons remained for 120 days attached to plants of Tabebuia aurea. Similarly, studies have shown that seedlings of M. urundeuva are able to maintain the cotyledons for a period of 90 days (Figueirôa et al 2004), while K. coriacea cotyledons may remain attached to the plant for up to six months (Nardoto et al 1998).…”
Section: Discussionmentioning
confidence: 94%
“…As camadas de esmalte foram colocadas nas regiões apical (A), mediana (M) e basal (B) de uma folha do 3º par (do ápice para a base), completamente expandida, de coloração e aspecto uniformes, nas superfícies adaxial e abaxial (Cabral et al 2004). Após secas, as camadas de esmalte foram removidas e montadas em laminas, em seguida levadas para microscópio binocular com aumento de 100 vezes.…”
Section: Methodsunclassified
“…Apesar de seu potencial para uma ampla utilização, existem poucos trabalhos referentes a seu crescimento inicial (SILVA e NOGUEIRA, 2003;CABRAL et al, 2004;PACHECO et al, 2008), necessitando, portanto, de mais estudos básicos e aplicados.…”
Section: Introductionunclassified